1997
DOI: 10.1292/jvms.59.1003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Canine Herpesvirus Glycoprotein D (Hemagglutinin).

Abstract: ABSTRACT. Glycoprotein D (gD) of canine herpesvirus (CHV) YP2 strain was expressed in COS-7 and insect (Spodoptera frugiperda; Sf9) cells. The gDs expressed in COS-7 and Sf9 cells reacted with a panel of monoclonal antibodies (MAbs) against CHV gD (hemagglutinin) and an MAb 25C9 against feline herpesvirus type 1 (FHV-1) gD by indirect immunofluorescence assay, and possessed a molecular weight (MW) of approximately 51-55 and 41-46 kilodalton (kDa), respectively, when examined by immunoblot analysis. After treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…canine RBC [15,19]. These interactions between gD and RBCs from the respective hosts might correlate with the host range of herpesvirus infection.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…canine RBC [15,19]. These interactions between gD and RBCs from the respective hosts might correlate with the host range of herpesvirus infection.…”
mentioning
confidence: 97%
“…Similarly, the host range of CHV is also very narrow [4]. A 47 kDa glycoprotein of CHV being responsible for HA was encoded by CHV gD gene [15,24], and cross-reacted with FHV-1 gD by an MAb 25C9 against FHV-1 gD [12]. This MAb possessed inhibition activities against both HAs by FHV-1 gD and CHV gp47 [12].…”
mentioning
confidence: 99%
“…The virus grows exclusively in cell types of only canine origin such as primary canine kidney cell cultures and Madin-Darby canine kidney (MDCK) cell line [6,10,62,78]. CHV gD adsorbs to canine RBC, not to feline RBC [47]. Although a common epitope is demonstrated between FHV-1 and CHV gDs by an MAb, which has a complement-independent VN activity to both viruses [36], different HA properties between these two gDs provide a notion that the gD may regulate the narrow host range of each virus at the cell-receptor levels.…”
Section: Hemagglutinin To Feline Red Blood Cell (Rbc)mentioning
confidence: 99%
“…All CHV strains were grown in Madin-Darby canine kidney (MDCK) cells for extraction We reported previously that canine herpesvirus (CHV) gD agglutinated canine red blood cells (RBC) and that this hemagglutination (HA) activity was inhibited by monoclonal antibodies (MAbs) against CHV gD [16,24,25]. Similarly, we reported that gD of feline herpesvirus type 1 (FHV-1) agglutinated feline RBC and cells expressing the gD adsorbed the RBC [13,14].…”
Section: Viruses and Cellsmentioning
confidence: 99%
“…One MAb 25C9 against FHV-1 gD recognized CHV gD by indirect immunofluorescence assay (IFA) and immunoblot analysis, and inhibited HA activity of CHV [12]. CHV gD agglutinates only canine RBC [16,19,24] while FHV-1 agglutinates only feline RBC [4,13,14,18]. The reason of these different HA activities has never been studied.…”
Section: Viruses and Cellsmentioning
confidence: 99%